Measurement of internal pressure and air flow during colonoscopy - Ishibashi, Fumiaki; Mochida, Kentaro; Morishita, Tetsuo; Nagai, Mizuki; Suzuki, Sho (Progress of Digestive Endoscopy, 2023)
Appropriate adjustment of the air volume is an important for performing endoscopy. However, Novice is often confused to adjust the appropriate air volume for performing endoscopy because air volume is subjective. If the adjustment can be assessed objectively, it will be possible to instruct the adjustment objectively to the novice. In this study, we tried to measure internal pressure in colon and flow volume inflated through endoscopy using an industrial pressure sensor and a flow sensor. We performed colonoscopy with controlling air volume while referring the internal pressure and flow volume displayed on the monitor. We conformed that the internal pressure changed directly according to flow air volume in colonoscopy insertion and removal. We successfully measured and displayed the internal pressure and flow volume during colonoscopy. The study has also limitation that number of subject is small and its clinical impact are not investigated. We would like to verify the clinical impact with collecting further data in the future.